Qualitative and Quantitative Ultrashort Echo Time Imaging of Musculoskeletal Tissues - Chang, Eric Y.; Du, Jiang; Bae, Won C.; Chung, Christine B. (Seminars in Musculoskeletal Radiology, 2015)
Ultrashort echo time (UTE) sequences represent a group of clinically compatible techniques that are capable of using echo times < 1 ms. With these techniques, direct imaging of short T2/T2* tissues or tissue components can now be performed. Continuing modifications to the UTE techniques have allowed for faster and more robust sequences now comparable with conventional clinical sequences. UTE also allows for morphological imaging and quantitative evaluation in a manner not previously possible with conventional imaging sequences utilizing much longer echo times. Numerous potential clinical applications have emerged that are discussed in this review article.
Keywords: magnetic resonance imaging; ultrashort echo time; UTE; short T2/T2*; musculoskeletal